BRAND IMAGE DAN LIFE STYLE DAPAT MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK ISOTONIK - Buci Morisson (KarismaPro, 2022)
This study aims to find out how the influence of brand image on the decision to purchase isotonic products in Sukabumi city and regency of Sukabumi. The sample used was 400 respondents, calculated based on Slovin's formula. The method of sampling respondents used in this study is through purposive sampling. Data collection method using survey method, with research instrument is questionnaire. The data analysis method uses statistical analysis in the form of multiple linear regression tests. Analysis tools using SPSS version 23 applications.  The results of this study showed that partially lifestyle variables had a positive and significant effect on the variable decision of purchasing isotonic beverages. While the variable brand image has a positive effect, but not significantly to the variable decision of purchasing isotonic beverage products